Revisiting The Mediating Role of Consumer Satisfaction: A Multivariate Analysis of Halal Labeling, Price, and Digital Marketing on Consumer Loyalty Among Gen Z in Indonesia - Mochlasin, Mochlasin; Utari, Dina (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2025)
This study investigates the mediating effect of consumer satisfaction on the relationship between halal labeling, price, and digital marketing, and consumer loyalty toward Hilo milk products among Generation Z consumers in Indonesia. Using a structured questionnaire and a purposive sampling approach, data were collected from 100 respondents aged 15–28 years in Salatiga, Central Java. Statistical analysis was conducted using SPSS, with reliability and validity checks, normality tests, multicollinearity analysis, and path analysis including the Sobel test to evaluate mediation. Findings indicate that while halal labeling shows no significant direct or indirect influence on consumer loyalty, both price and digital marketing significantly enhance consumer satisfaction, which in turn positively mediates their impact on loyalty. The model explains 47.7% of the variance in consumer satisfaction and 45.2% in consumer loyalty. These results provide managerial implications for halal food producers to shift focus from certification-centered marketing to consumer-centric strategies emphasizing affordability and digital engagement. This study contributes to the limited empirical literature on Muslim Gen Z consumption behavior in Southeast Asia.